Nursing auditing in the face of quality of care in the public hospital environment (Research, Society and Development, 2023)
The objective of this study was to analyze what has been produced in the scientific literature on nursing auditing in relation to the quality of care in the public hospital environment. This is an integrative literature review, carried out through direct consultation on the internet through the online data available in the Virtual Health Library (VHL), in the following databases: Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SciELO), and Nursing Database (BDENF), totaling 15 articles. The results showed that the Nurse Auditor within the hospital unit first needs to perform an analysis of the medical records. Therefore, the nursing audit service is an essential part for the evaluation of the nursing team, as well as the quality of care.